Orchestration of innovative networks in public policies: The Economic Clusters of Innovation Program from the Government of The State of Ceará - Cavalcante, Roberta Feitosa de Lucena; Buarque, Brenno; Câmara, Samuel Façanha (Contextus - Revista Contemporânea de Economia e Gestão, 2023)
This research has the objective of presenting the context of the Economic Clusters of Innovation Program (ECIP) as an orchestrating project of public innovative networks, analyzing how the Program used orchestration constructs in its relationship, constituted by different actors (Universities, Government, Researchers, Entrepreneurs and Policy-makers) that formed the public policy. For data collection, semi-structured interviews were conducted with thirty actors from local innovative ecosystems. Among the results obtained, it is concluded that the ECIP encouraged and managed interactions in a systematic and significant way among its actors, generating a great positive impact on the innovation results of the network.